New Zealand : Financial Sector Assessment Program: Technical Note-Contingency Planning and Crisis Management Framework. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note assesses the level of implementation of the Contingency Planning and Crisis Management Framework in New Zealand. Work has already begun to identify necessary resources, such as rosters of potential statutory managers and personnel from government agencies and the private sector who could be mobilized to deal with a crisis. This work needs to be further developed. In parallel, the Reserve Bank of New Zealand should continue to document the procedure for appointment of a statutory manager, open bank resolution, and other resolution options. The Treasury should complete 'shelf' agreements, which may be required for a Crown guarantee or other support in a crisis.